Back to the beginning scene of the fight between Rama and the demon army - MetMuseum (2022)
Drawn from the third book (“Aranya Kanda”) of the Ramayana, the elaborate narrative on this vessel depicts key scenes in the Dandaka forest. Created by the Bombay School of Art in an effort to preserve Indian craft, the object features many embellishing motifs drawn from the Buddhist murals of Ajanta. These features include the lotus and pearl band running around the shoulder and the monster faces (kirtimukha), set between the addorsed elephant heads, that spit out a garland of jewels. Although the vase is grounded in the Indian tradition, British neoclassical taste clearly underlies its shape and some of its geometric motifs. Given the scale and inscribed multiscene narrative, this vase may have been produced for the London Colonial and Indian Exhibition of 1886.